Herança da resistência do acesso AM-55 de meloeiro à podosphaera xanthii - Martins, Adriano Ferreira (Universidade Federal Rural do Semi-Árido, 2019)
Melons are one of the most economically important crops in Brazil. The Northeast Region was responsible for approximately 95% of the national production and exportation in 2017, with the states of Rio Grande do Norte and Ceará being the main producers. Parallel to the success of cultivation in the region is the occurrence of diseases that reduce fruit production and quality. Among leaf diseases that affect melons, Powdery Mildew stands out. Powdery Mildew caused by the fungal species Podosphaera xantii is a severe disease that causes significant losses in the melon (Cucumis melo L.) production worldwide. The use of resistant cultivars is one of the main options for the management of this pathogen, since it is easily adopted by the producer with a pathogen management program. For introgression of alleles into breeding programs, it is necessary to know how genetic resistance control occurs. Studies on inheritance allows the breeder to choose the best strategy for obtaining resistant cultivars with the least resources and time. Therefore, the objective of the present work was to study the resistance inheritance of the AM-55 accession of melons to P. xantii, in crossbreeding with the susceptible cultivar 'Vedrantais' under agricultural greenhouse conditions. Initially the F1 generation was obtained, and later the F2 segregating generation. The inoculation was done by depositing fungus structures (hyphae and conidiophores) on the adaxial part of the third true leaf of the plant. Fifteen days after inoculation the evaluation was performed on a scale of 1 to 4 grades. Plants with grades 1 and 2 were considered resistant, while plants with grades 3 to 4 were susceptible. To explain the inheritance of resistance, a probable model was adopted using the Chi-square test using an experimental error of 5% (α = 0.05). The inheritance of melon AM-55 access resistance is monogenic and recessive in relation to P. xantii recas 3.5 and 5. The introgression of resistance alleles into susceptible strains can be done by successive backcrosses.
Monografia
Keywords: Oídio; Monogênica; Cucumis melo; Alelo; Powdery mildew; Monogenic; Cucumis melo; Allele; CIENCIAS AGRARIAS::AGRONOMIA